Macular Choroidal Thickness in Patients with Ocular Hypertension as Assessed Using Enhanced Depth Imaging Optical Coherence Tomography - Pinar Topcu-Yilmaz; Ozlem Gürbüz Köz; Alper Yarangumeli; Mehmet Numan Alp (Beyoglu Eye Journal, 2019)
INTRODUCTION[|]The aim of this study was to evaluate the macular choroidal thickness (CT) in patients with ocular hypertension (OHT) using spectral domain optical coherence tomography (SD-OCT) and compare the results with healthy individuals.[¤]METHODS[|]Thirty eyes of 30 patients newly diagnosed with OHT and 24 eyes of 24 healthy controls were included in this cross-sectional study. After a detailed ophthalmological examination, macular CT was measured with enhanced depth imaging optical coherence tomography (EDI-OCT) (Cirrus HD-OCT, Carl Zeiss Meditec AG, Jena, Germany) at the fovea and at positions 500 µ, 1000 µ, 1500 µ nasal and temporal to the fovea. The Mann-Whitney U test was used to compare the CT measurements between groups. The correlation between the mean deviation, pattern standard deviation, and retinal nerve fiber layer thickness (RNFL) and CT was evaluated with the Spearman correlation coefficient. Statistical significance was accepted as p<0.05. [¤]RESULTS[|]The mean CT in the OHT group was significantly thinner than that of the controls at locations 1000 µ (250.13+-69.53µ vs 275.92+-47.34µ; p=0.02) and 1500µ (236.03+-65.44µ vs 265.46+-47.56µ; p=0.009) temporal to the fovea. The CT at the other measurement points was also thinner in eyes with OHT, but the difference failed to reach statistical significance. A moderately negative correlation was detected between the mean deviation and CT at locations 1000µ (r=-0.42; p=0.03) and 1500µ (r=-0.44; p=0.02) temporal to the fovea There was a moderate correlation between the average RNFL thickness and CT at locations 500µ (r=0.44; p=0.03), 1000µ (r=0.42; p=0.04) and 1500µ (r=0.56; p=0.005) temporal to the fovea. [¤]DISCUSSION AND CONCLUSION[|] In the present study, the macular CT was thinner in patients with OHT and this thinning was statistically significant at the temporal macula. A longitudinal, prospective study involving multiple EDI-OCT measurements is required to further understand the relationship. [¤]